Antioxidant Activity and Polyphenol Content of Brassica oleracea Varieties. Issue 4 (3rd July 2016) - Upadhyay, Rohit; Sehwag, Sneha; Singh, Satyendra P.
ABSTRACT: Reasons for beneficial medicinal benefits to humans from cabbage ( Brassica oleracea L. var. capitata ) needs clarification. The research examined beneficial phytochemicals in cabbage that activate and stabilize antioxidant and detoxification mechanisms in humans. Methanolic extracts of red cabbage ( B. oleracea L. var. capitata f. rubra [MERC]), green cabbage ( B. oleracea L. var. capitata [MEGC]), cauliflower ( B. oleracea L. var. botrytis [MEC]), and broccoli ( B. oleracea L. var. italica [MEB]) were analyzed for antioxidant activity (AA) using different in vitro assays and polyphenol content. The AA was tested by radical scavenging activity of extracts against 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and hydroxyl radical, ferric reducing power, and ferrous ion chelation assay. The antioxidant activity from all assays was in the order MERC > MEGC > MEB > MEC. Total phenolic and flavonoid contents were highest and lowest for MERC (2.26 mg gallic acid equivalent [GAE]·g −1 fresh weight [FW] and 1.43 mg rutin equivalent [RE]·g −1 FW) and MEC (0.83 mg GAE·g −1 FW and 0.42 mg RE·g −1 FW), respectively, as were antioxidant assays. High-performance liquid chromatography analyses of extracts indicated presence of phenolic acid and flavonoid compounds confirming in vitro antioxidant behavior. There may be a rational for use of B. oleracea, especially red and green cabbage, in phytomedicine as a food supplement against diseases that involve free radicals.